Pediatric congenital buttock sinus tract:10-year experience in a single institution - Kai Wang; Chunhui Peng; Wenbo Pang; Dayong Wang; Tingchong Zhang; Zengmeng Wang; Dongyang Wu; Yajun Chen (BMC, 2019)
Abstract Purpose To review our experience with pediatric congenital buttock sinus tract, and to conclude the clinical characteristics and management of the disease. Methods Twenty-two pediatric patients diagnosed with congenital buttock sinus tract were included. Medical records were reviewed, and the patients were followed up. Continuous variables were presented by median and range. Categorical variables were presented as frequencies and percentages. Results Among the 22 patients, there were 8 boys (36.4%) and 14 girls (63.6%). The median first onset age was 42 months, and the range was 5 months to 12 years old. Admission age was 69.5 months, with a range from 14 months to 12 years old. Overall prior treatment time was 11 months, ranging from 3 months to 11 years. Twenty-one patients had definite congenital dimples since birth, and later manifested with infection through the dimple. All patients came to the doctor with complaint of the infection. The number of invasive procedures ranged from 0 to 5, with an average of 2. Radiology could exactly display the morphology and show the termination as a retrorectal cyst. The surgical procedure was adopted trans-fistula tract, and the pathological results showed a dermoid cyst in 11 patients and an epidermoid cyst in 10 patients. During the follow-up period of 34.5 months (range, 2 months to 8 years), 19 patients were uneventful and 3 patients suffered recurrence. Two of them underwent a second operation and had no recurrence ever since. The third patient did not receive a second operation, and the refractory infection was still present. Conclusions Pediatric congenital buttock sinus tract is rare and has a female predominance in the morbidity. Patients have a distinctive congenital dimple on the buttock with recurrent infection, and there usually exists a congenital sinus tract from the dimple to the retrorectal space. Total excision is the only method for the cure. The nature of the disease is a retrorectal developing dermoid cyst or epidermoid cyst.